Orexin deficiency modulates cognitive flexibility in a sex‐dependent manner. (3rd November 2020) - Durairaja, Archana; Fendt, Markus
Abstract: Cognitive flexibility is an important executive function and refers to the ability to adapt behaviors in response to changes in the environment. Of note, many brain disorders are associated with impairments in cognitive flexibility. Several classical neurotransmitter systems including dopamine, acetylcholine and noradrenaline are shown to be important for cognitive flexibility, however, there is not much known about the role of neuropeptides. The neuropeptide orexin, which is brain‐widely released by neurons in the lateral hypothalamus, is a major player in maintaining sleep/wake cycle, feeding behavior, arousal, and motivational behavior. Recent studies showed a role of orexin in attention, cognition and stress‐induced attenuation of cognitive flexibility by disrupting orexin signaling locally or systemically. However, it is not known so far whether brain‐wide reduction or loss of orexin affects cognitive flexibility. We investigated this question by testing male and female orexin‐deficient mice in the attentional set shifting task (ASST), an established paradigm of cognitive flexibility. We found that orexin deficiency impaired the intra‐dimensional shift phase of the ASST selectively in female homozygous orexin‐deficient mice and improved the first reversal learning phase selectively in male homozygous orexin‐deficient mice. We also found that these orexin‐mediated sex‐based modulations of cognitive flexibility were not correlated with trait anxiety, narcoleptic episodes, and reward consumption. Our findings highlight a sexually dimorphic role of orexin in regulating cognitive flexibility and the need for further investigations of sex‐specific functions of the orexin circuitry. Abstract : Orexin deficiency attenuated cognitive flexibility, measured by the attentional set shifting task, in a sex‐dependent manner. In females, homozygous orexin‐deficient mice showed impaired learning performance (higher number of trials to criterion) in the intra‐dimensional shift phase (IDS). In males, homozygous orexin‐deficient mice showed improved learning performance in the reversal 1 phase (Rev1).